Stars-- the inside story - World Book, Inc (Chicago World Book, 2010)
An introduction to stars with information about their age, size, colors, and other characteristics. Includes diagrams, fun facts, glossary, resource list, and index"--Provided by publisher
Includes bibliographical references (p. 62) and index
Hurg
5 8
Keywords: Stars -- Juvenile literature